Causal agents responsible for the die-back of Dalbergia sissoo in Nepal's eastern Tarai - Parajuli, A.V.; Bhatta, B.; Adhikari, M.K.; Tuladhar, J.; Thapa, H.B. (Banko Janakari, 2017)
Abstract on the PDF